2008
DOI: 10.1021/jp803984f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics of Polarons in Conductive Polyaniline: Comparison of Primary and Secondary Doped Forms

Abstract: Time-and wavelength-resolved pump-probe measurements are performed on the conductive, primary and secondary doped, forms of polyaniline in solution to investigate the relaxation dynamics of photoexcited polarons. Contrasting dynamics observed in the two forms allow investigation of electronic (and structural) relaxation of this material. Pump pulse at 800 nm photoexcites an electron from the valence to polaron band, and subsequent relaxation dynamics are probed by a white light continuum pulse. Three distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 77 publications
2
32
2
Order By: Relevance
“…In our experiments the data from the interval of 425-650 nm and also for 400 nm excitation was recorded for the first time. We note that specific features detected near 460 nm cannot be explained by a model proposed in [10], other discrepancies were outlined in our recent publication [11].…”
Section: Methodscontrasting
confidence: 48%
See 2 more Smart Citations
“…In our experiments the data from the interval of 425-650 nm and also for 400 nm excitation was recorded for the first time. We note that specific features detected near 460 nm cannot be explained by a model proposed in [10], other discrepancies were outlined in our recent publication [11].…”
Section: Methodscontrasting
confidence: 48%
“…As this delayed signal overlaps with a cross-correlation feature near time zero, a kind of a dip is formed (indicated by an arrow in Fig. 3) [10,11]. Such a behavior is common for all decay traces in the interval 900-1050 nm.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Secondary doping, in turn, creates a topologically less distorted structure [16][17][18]. It was reported that films of secondary doped PANI prepared by a novel synthetic method exhibit the hallmark of metallic conductivity, that is, a monotonic increase in conductivity with temperature [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The conjugated π structure enables the mobility of polarons along the length of the molecule. This mobility accounts for the intrachain conductivity of polyaniline [21]. Polarons in polyaniline follow the traditional definition applying to polarons in a crystal lattice, in that the polaron exists as an electric field and a conformational distortion.…”
Section: Conductivitymentioning
confidence: 99%